Epigenetic silencing of CREB3L1 by DNA methylation is associated with high-grade metastatic breast cancers with poor prognosis and is prevalent in triple negative breast cancers. Issue 1 (December 2016) - Ward, Alison; Mellor, Paul; Smith, Shari; Kendall, Stephanie; Just, Natasha; Vizeacoumar, Frederick; Sarker, Sabuj; Phillips, Zoe; Alvi, Riaz; Saxena, Anurag; Vizeacoumar, Franco; Carlsen, Svein; et al.
Abstract Background CREB3L1 (cAMP-responsive element-binding protein 3-like protein 1), a member of the unfolded protein response, has recently been identified as a metastasis suppressor in both breast and bladder cancer. Methods Quantitative real time PCR (qPCR) and immunoblotting were used to determine the impact of histone deacetylation and DNA methylation inhibitors on CREB3L1 expression in breast cancer cell lines. Breast cancer cell lines and tumor samples were analyzed similarly, and CREB3L1 gene methylation was determined using sodium bisulfite conversion and DNA sequencing. Immunohistochemistry was used to determine nuclear versus cytoplasmic CREB3L1 protein. Large breast cancer database analyses were carried out to examine relationships between CREB3L1 gene methylation and mRNA expression in addition to CREB3L1 mRNA expression and prognosis. Results This study demonstrates that the low CREB3L1 expression previously seen in highly metastatic breast cancer cell lines is caused in part by epigenetic silencing. Treatment of several highly metastatic breast cancer cell lines that had low CREB3L1 expression with DNA methyltransferase and histone deacetylase inhibitors induced expression of CREB3L1, both mRNA and protein. In human breast tumors, CREB3L1 mRNA expression was upregulated in low and medium-grade tumors, most frequently of the luminal and HER2 amplified subtypes. In contrast, CREB3L1 expression was repressed in high-grade tumors, and its loss was most frequently associated with triple negative breast cancers (TNBCs). Importantly, bioinformatics analyses of tumor databases support these findings, with methylation of the CREB3L1 gene associated with TNBCs, and strongly negatively correlated with CREB3L1 mRNA expression. Decreased CREB3L1 mRNA expression was associated with increased tumor grade and reduced progression-free survival. An immunohistochemistry analysis revealed that low-grade breast tumors frequently had nuclear CREB3L1 protein, in contrast to the high-grade breast tumors in which CREB3L1 was cytoplasmic, suggesting that differential localization may also regulate CREB3L1 effectiveness in metastasis suppression. Conclusions Our data further strengthens the role for CREB3L1 as a metastasis suppressor in breast cancer and demonstrates that epigenetic silencing is a major regulator of the loss of CREB3L1 expression. We also highlight that CREB3L1 expression is frequently altered in many cancer types suggesting that it could have a broader role in cancer progression and metastasis.